A New Translation Operator by Covariant Derivative in the Generalized Space - Mehdi Jafari Matehkolaee; Houshyar Noshad (Advances in Mathematical Physics)
In this paper, we substituted the ordinary derivative with the covariant derivative in simple translation, that is built by applying the ordinary derivative and we investigate the new display of the simple translation. We have introduced a new translation operator in which its generator is exactly covariant derivative. To know the translation of a quantum particle around a space where the effect of gravity is significant, such as a black hole, it is enough to put the metric of that space in the translation derived in this paper.